Evaluation of antioxidant activity of Melittis melissophyllum L. extracts - Grujić Slavica M.; Stojanović Gordana S.; Mitić Violeta D.; Stankov-Jovanović Vesna; Džamić Ana M.; Alimpić Ana Z.; Marin Petar D. (Archives of Biological Sciences, 2014)
The antioxidant activities of methanol and ethanol (10%, 30%, 50% and 96%) extracts of the aerial parts of Melittis melissophyllum L. were determined by DPP H, ABTS and FRAP assays. The content of flavonoids and phenols was also investigated. The total phenolic content in the extracts was determined using Folin-Ciocalteu assay; their amounts ranged between 63.5 and 111.7 mg GAeqv/g, while the concentrations of flavonoids were from 7.33 to 56.00 mg Queqv/g. IC50 values of the DPP H scavenging effect were from 0.109 to 0.664 mg/mL. The DPP H scavenging effect of the extracts was determined and the obtained IC50 values were from 0.109 to 0.664 mg/mL of solution. The values of ABTS radical activity were from 0.45 to 0.89 mg ascorbic acid/g. The FRAP value was within the range 0.160-0.382 mmol Fe/mg. The obtained values were analyzed by means of multivariate analysis, employing a hierarchical cluster analysis and between-groups linkage. The presented results confirmed that M. melissophyllum possesses good antioxidant properties and may serve as a promising source of natural antioxidants. [Projekat Ministarstva nauke Republike Srbije, br. 173029]